Answer:
-3x+30
Step-by-step explanation:
![4\left(x+7\right)-7x+2](https://tex.z-dn.net/?f=4%5Cleft%28x%2B7%5Cright%29-7x%2B2)
Expand ![4(x+7)= 4x+28](https://tex.z-dn.net/?f=4%28x%2B7%29%3D%204x%2B28)
![4x+28-7x+2](https://tex.z-dn.net/?f=4x%2B28-7x%2B2)
Simplify ![4x+28-7x+2](https://tex.z-dn.net/?f=4x%2B28-7x%2B2)
![-3x+30](https://tex.z-dn.net/?f=-3x%2B30)
Answer:
![3.01 * 10^2](https://tex.z-dn.net/?f=3.01%20%2A%2010%5E2)
Step-by-step explanation:
=)
Hope this helps!
The difference of the expression
is ![\frac{2x^5(x + 3) - 3x^5}{x(x - 3)(x + 3)}](https://tex.z-dn.net/?f=%5Cfrac%7B2x%5E5%28x%20%2B%203%29%20-%203x%5E5%7D%7Bx%28x%20-%203%29%28x%20%2B%203%29%7D)
<h3>How to determine the difference?</h3>
The expression is given as:
![\frac{2x^5}{x^2 - 3x} - \frac{3x^5}{x^3 - 9x}](https://tex.z-dn.net/?f=%5Cfrac%7B2x%5E5%7D%7Bx%5E2%20-%203x%7D%20-%20%5Cfrac%7B3x%5E5%7D%7Bx%5E3%20-%209x%7D)
Factor the denominators of the expressions:
![\frac{2x^5}{x(x - 3)} - \frac{3x^5}{x(x^2 - 9)}](https://tex.z-dn.net/?f=%5Cfrac%7B2x%5E5%7D%7Bx%28x%20-%203%29%7D%20-%20%5Cfrac%7B3x%5E5%7D%7Bx%28x%5E2%20-%209%29%7D)
Apply the difference of two squares to x² - 9
![\frac{2x^5}{x(x - 3)} - \frac{3x^5}{x(x - 3)(x + 3)}](https://tex.z-dn.net/?f=%5Cfrac%7B2x%5E5%7D%7Bx%28x%20-%203%29%7D%20-%20%5Cfrac%7B3x%5E5%7D%7Bx%28x%20-%203%29%28x%20%2B%203%29%7D)
Take LCM
![\frac{2x^5(x + 3) - 3x^5}{x(x - 3)(x + 3)}](https://tex.z-dn.net/?f=%5Cfrac%7B2x%5E5%28x%20%2B%203%29%20-%203x%5E5%7D%7Bx%28x%20-%203%29%28x%20%2B%203%29%7D)
Hence, the difference of the expression
is ![\frac{2x^5(x + 3) - 3x^5}{x(x - 3)(x + 3)}](https://tex.z-dn.net/?f=%5Cfrac%7B2x%5E5%28x%20%2B%203%29%20-%203x%5E5%7D%7Bx%28x%20-%203%29%28x%20%2B%203%29%7D)
Read more about expressions at:
brainly.com/question/723406
#SPJ4
Answer:
1111111 is the answer
Step-by-step explanation:
6x + 3y = 79.5
3x + 2y = 41 y = -3/2x + 41/2 y = -1.5x + 20.5
6x + 3(-1.5x + 20.5) = 79.5
6x - 4.5x + 61.5 = 79.5
1.5x + 61.5 = 79.5
1.5x = 18
x = 12
Each shirt costs $12.
Now insert that number into the x to find the cost of each tie.
3(12) + 2y = 41
36 + 2y = 41
2y = 5
y = 2.5
Each tie costs $2.50.